2021
DOI: 10.1021/acsami.0c21710
|View full text |Cite
|
Sign up to set email alerts
|

Reduction-Responsive Chemo-Capsule-Based Prodrug Nanogel for Synergistic Treatment of Tumor Chemotherapy

Abstract: Chemotherapy is currently the most universal therapeutics to tumor treatment; however, limited curative effect and undesirable drug resistance effect are the two major clinical bottlenecks. Herein, we develop a two-in-one cross-linking strategy to prepare a stimuli-responsive prodrug nanogel by virtue of delivering a combination of chemotherapeutic drugs of 10-hydroxy camptothecin and doxorubicin for ameliorating the deficiencies of chemotherapy and amplifying the cancer therapeutic efficiency. The obtained pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The reductive agent glutathione was the factor responsible for releasing the drug effectively (Figure 5C,D). The studies and results show that the combined effects of 10-hydroxy camptothecin (HCPT) and doxorubicin (DOX) contribute to the apoptosis process through the topoisomerase pathway, which improves the inhibitory effect in tumor growth [122]. (Reproduced with the permission from ref.…”
Section: Functionalized Role Of Nanohydrogelsmentioning
confidence: 99%
“…The reductive agent glutathione was the factor responsible for releasing the drug effectively (Figure 5C,D). The studies and results show that the combined effects of 10-hydroxy camptothecin (HCPT) and doxorubicin (DOX) contribute to the apoptosis process through the topoisomerase pathway, which improves the inhibitory effect in tumor growth [122]. (Reproduced with the permission from ref.…”
Section: Functionalized Role Of Nanohydrogelsmentioning
confidence: 99%
“…In another study, the in vivo synergistic antitumor efficiency of HSD NGs was assessed in 4T1 tumor-bearing mice, and results indicated that HSD NGs enhanced apoptosis and tumor accumulation, and suppressed tumor growth and volume [ 68 ].…”
Section: Anticancer Activities Of Camptothecin Nano-formulationsmentioning
confidence: 99%
“…According to research data, the concentration of GSH in tumor cells reaches 2-10 mM, while the concentration in normal tissues is merely around 2-20 μM (Yuan et al, 2018;Kumar et al, 2019). Based on this, Lu developed a two-in-one cross-linking strategy to prepare GSH-responsive prodrug nanogels by coupling DOX and CPT using disulfide compound as crosslinker agent (Lu et al, 2021). Under the high concentration of GSH in tumor, both DOX and CPT released about 75% within 48 h in physiological pH 7.4.…”
Section: Redox-sensitive Nanogelsmentioning
confidence: 99%